Water balance - stream water level from Tarfalajokk, Stream level & Discharge, 2018-05-28–2018-09-16 - Tarfala Research Station (Stockholm University, 2021)
Accurate measurements of the stream level of the main inflow and outflow of the lakes of SITES Water and streams within the research station catchment.
Tarfala Research Station (2021). Water balance - stream water level from Tarfalajokk, Stream level & Discharge, 2018-05-28–2018-09-16 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/aSp5HC97V_7GygSoqubAbzYq
Keywords: Tarfala Research Station; Stream; Time instant; Time instant; Stream level; Stream level; Water temperature; Water temperature; Electrical conductivity; Electrical conductivity; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap